2018
DOI: 10.1111/jnu.12389
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management in the Pediatric Palliative Care Population

Abstract: A better understanding of current research on pain in the pediatric palliative care population can improve patient care and lead to better research in this specialty field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…Therefore, care should be taken in the development of EMR in PPC documentation of symptoms to ensure the specific requirements in PPC [57]. In this context, scales specific to the paediatric population must be used for the external assessment of pain, such as the paediatric pain questionnaire [58].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, care should be taken in the development of EMR in PPC documentation of symptoms to ensure the specific requirements in PPC [57]. In this context, scales specific to the paediatric population must be used for the external assessment of pain, such as the paediatric pain questionnaire [58].…”
Section: Discussionmentioning
confidence: 99%
“…Pain, from the disease or interventions, is the most common symptom experienced by critically ill children in PICU (27,28). Other commonly experienced symptoms are nausea, dyspnea and delirium.…”
Section: Pain and Symptom Managementmentioning
confidence: 99%
“…Although the primary goal of pediatric palliative care is to improve pain in children, hospitalized children still experience severe unrelieved pain (Wolfe et al, 2015). Although pain may decrease after a referral to palliative care, researchers have identified that between 31% and 60% of hospitalized children receiving palliative care still struggle with significant pain (Bogetz, Schroeder, et al, 2014; Shaw, 2012; Thomas et al, 2018). The advances and success of medical science and medical care have resulted in a growing number of children living with long-term and/or life-limiting chronic conditions.…”
Section: Introductionmentioning
confidence: 99%